2018
DOI: 10.1186/s12873-018-0159-4
|View full text |Cite
|
Sign up to set email alerts
|

High inter-observer agreement of observer-perceived pain assessment in the emergency department

Abstract: BackgroundTriage is used to prioritize the patients in the emergency department. The majority of the triage systems include the patients’ pain score to assess their level of acuity by using a combination of patient reported pain and observer-perceived pain; the latter therefore requires a certain degree of inter-observer agreement.The aim of the present study was to assess the inter-observer agreement of perceived pain among emergency department nurses and to evaluate if it was influenced by predetermined fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The Authors conclude that their findings justify that nurse-perceived pain assessment is used for triage in the emergency department. 20 One major concern has been driven by the fact that, despite declaring a high NRS score, several patients refuse analgesia delivered by the triage nurse. In an interesting study conducted in France, 38% of patients refused analgesia at triage, mainly (53%) because Pain is bearable without analgesic.…”
Section: Discussionmentioning
confidence: 99%
“…The Authors conclude that their findings justify that nurse-perceived pain assessment is used for triage in the emergency department. 20 One major concern has been driven by the fact that, despite declaring a high NRS score, several patients refuse analgesia delivered by the triage nurse. In an interesting study conducted in France, 38% of patients refused analgesia at triage, mainly (53%) because Pain is bearable without analgesic.…”
Section: Discussionmentioning
confidence: 99%
“…As Hicks et al (2001) 51 have demonstrated that the Faces Pain Scale Revised (FPS‐R) is an appropriate tool for children's pain intensity in children aged 4 and up, we decided to use this scale rather than the NRS‐11 in the age group 4‐8. Clinically significant pain was defined as a score ≥ 4 on the NRS or the FPS‐R (face number 3 equals a score of 4) on either “worst pain” or “average pain in the last 24 h.” 52,53 …”
Section: Methodsmentioning
confidence: 99%
“…Since then, it has also been used in children. 47,48 Stinson et al (2015) 49 For the purposes of this study, the Dutch version of the BPI-SF has been slightly changed and adapted to the participants (ie, children equals a score of 4) on either "worst pain" or "average pain in the last 24 h." 52,53 The pain management section of the BPI-SF consists of one openended item in which treatments/medications received for the pain are assessed (ie, "What treatments or medications did you receive for your pain/did your child receive for their pain?"). Afterwards, responses were dichotomized to assess whether any pain treatments/medications were used (yes/no categories).…”
Section: Brief Pain Inventory Short Formmentioning
confidence: 99%
“…The family version of the app allowed children (aged [8][9][10][11][12][13][14][15][16][17][18] or parents (children aged 0-7) to report pain intensity at the time on an 11-point numeric rating scale (NRS-11) ranging from 0 (no pain) to 10 (worst pain imaginable). When a score ranging between 0 and 3 was reported, families were redirected to interventions suitable to the home setting on the psycho-educational information page of the app.…”
Section: The Klik Pain Monitor Appmentioning
confidence: 99%
“…Studies on pain management at home reveal parental misconceptions (e.g., pain is unavoidable during cancer) [1] and concerns regarding analgesic use (e.g., pain medication is addictive) [11]. A previous study in children (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years old) receiving outpatient chemotherapy revealed that in one third of clinically significant pain incidents (score ≥ 4 on scale of 0-10 [12,13]) occurring in the home setting, no analgesic medication was used [5]. It seems that despite the availability of effective pain interventions (either pharmacologic [14,15] or nonpharmacologic [16][17][18][19] in nature) for children with cancer, parents tend to undertreat pain [3].…”
Section: Introductionmentioning
confidence: 99%